Study on naked eye tracing of inguinal sentinel lymph nodes in penile cancer patients with carbon nanoparticle suspension injection - Liu, Chengyi; Xu, Pengcheng; Shao, Song; Yang, Mingshan; Li, Chao; Li, Shuangjie; Liu, Wei; Ding, Xiaobo; Ma, Jici; Li, Guangyuan (Frontiers in Medicine, 2023)
Objective: Exploratory study of the effect and clinical value of carbon nanoparticle suspension injection(CNSI) as a tracer for inguinal sentinel lymph nodes in penile cancer. Method: We selected 29 patients with penile cancer in our department from January 2019 to October 2022. According to whether the CNSI tracer was injected during the pathological biopsy of the inguinal lymph nodes, the enrolled patients were assigned to the control group, the group in which CNSI was injected 12 hours before the surgery (12HBS group) and the group in which CNSI was injected 0.5 hour before the surgery(0.5HBS group). Evaluating the effectiveness of CNSI as a lymphatic tracer involves analysing the following: its safety, the statistical analysis of the detection rate(DR) of different groups, the number of lymph nodes sent for each case(NOLNSFEC), the difference of positive rate of lymphatic metastasis(PROLM), and operation time(OT). Results: The lymph nodes in the 12HBS group and 0.5HBS group had an obvious black staining appearance, and no adverse reactions or surgical complications were found. Most of the black-stained areas caused by CNSI injection were removed with penile excision, which did not affect the postoperative appearance. This did not affect the pathological analysis. The DR of lymph nodes in the 12HBS group was higher (P<0.05) than that in the control group. More lymph nodes were removed for examination (P<0.05), which improved the efficiency of surgery. Compared with the 12HBS group, the number of lymph nodes removed in the 0.5HBS group decreased (P<0.05). The OT was shortened (P<0.05), but there was no significant difference in the DR and PROLM. Conclusion: CNSI was applied to the naked-eye tracing of inguinal sentinel lymph nodes in penile cancer, which is safe and efficient. Injection of CNSI 0.5 hour before surgery can help identify the “foremost position” of sentinel lymph nodes and reduce surgical trauma.